Hyperecho-turbo spin-echo sequences at 3T: clinical application in neuroradiology. - Tetzlaff, R; Mader, I; Küker, W; Weber, J; Ziyeh, S; Schulze-Bonhage, A; Hennig, J; Weigel, M (2008)
BACKGROUND AND PURPOSE: Hyperecho-turbo spin-echo (hyperTSE) sequences were developed to reduce the specific absorption rate (SAR), especially at high fields such as 3T and above. The purpose of this study was to quantitatively and qualitatively assess the detection of neuroradiologic pathologies by hyperTSE in comparison with standard turbo spin-echo (TSE180 degrees) sequences. MATERIALS AND METHODS: TSE180 degrees and hyperTSE images with parameters adapted for equal T2 contrast were acquired on a 3T whole-body system in 51 patients with 54 cerebral pathologies. Region-of-interest analysis was performed of signal intensities of pathologies, normal white and gray matter, CSF, and the SD of noise. Signal intensity-to-noise ratios (SNRs) and contrast-to-noise ratios (CNRs) for healthy tissues and pathologies were determined. A qualitative rating concerning artifacts, lesion conspicuity, and image quality was performed by 2 experienced neuroradiologists. RESULTS: HyperTSE sequences were equivalent to standard TSE180 degrees sequences for the CNR of pathologies and of the contrast between gray and white matter. The SNR of gray and white matter and CSF were also the same. The CNRs of the pathologies in hyperTSE and TSE180 degrees images were strongly correlated with each other (r = 0.93, P = .001). The visual rating of images revealed no significant differences between hyperTSE and TSE180 degrees. CONCLUSION: HyperTSE sequences proved to be qualitatively and quantitatively equivalent to TSE180 degrees sequences in the detection of high- and low-signal-intensity lesions. They provide equal CNR of pathologies and of gray minus white matter and reduce the imaging restrictions of conventional TSE180 degrees imposed by SAR limitations at 3T.